THE SURVIVAL OF ACCRUED DELAY PENALTIES AFTER CONTRACT TERMINATION UNDER SERBIAN LAW - Karanikić Mirić, Marija (Pravni zapisi, 2026)
This article examines whether creditors lose the right to an accrued con- tractual penalty for delay upon termination of the contract for breach. The Serbian Law on Obligations (LO) contains no provision extinguishing that right upon termination. Penalties survive termination based on the systematic reading of the LO, legal doctrine, judicial practice, comparative materials, and the role of contractual penalties in commercial practice. A contractual penalty is accessory at inception; once due, however, it becomes an independent right. Delay gives rise to legal consequences that termination does not erase retroactively. Just as termination does not affect accrued default interest or damages, it does not affect the accrued amount of a contractual penalty for delay, but only prevents its further increase. The contrary view would force the creditor to choose between terminating the contract to obtain restitution and retaining the right to the penalty.